Analisis kekuatan dan stabilitas struktur trolley terhadap variasi beban statis menggunakan metode elemen hingga (FEA) - Khafidh Deedat Alnurrasyid (BKS-TM Indonesia, 2025)
This study aims to evaluate the strength and stability of a trolley frame subjected to static loading using the Finite Element Analysis (FEA) approach. A three-dimensional model of the trolley was developed in SolidWorks and analyzed under three loading conditions: 8,000 N, 10,000 N, and 12,000 N. S45C steel was selected due to its mechanical properties suitable for structural applications. The analysis focused on key parameters, including von Mises stress, total deformation, and safety factor, to obtain a comprehensive understanding of the structural response. The simulation results indicate that all maximum stress values remain well below the material’s yield strength, ensuring that the structure behaves elastically. Total deformation increases linearly with the applied load, indicating that the frame has not exhibited any permanent deformation or signs of potential failure. The safety factor values range from 3.05 to 4.52, indicating that the design maintains a high safety margin under varying load conditions. This research is essential because trolleys serve as a primary material-handling tool in industrial environments, requiring a structure that is strong, stable, and safe to ensure smooth operations and prevent failures that may hinder productivity. Through FEA-based analysis, actual working conditions can be accurately simulated, allowing the frame design to be validated prior to manufacturing and serving as a technical foundation for further design improvements.